Architectural and Infrastructure Intervention Priorities for Community Based Ecotourism Villages Using A 4a Moora Model: North Sulawesi, Indonesia - Rompas, Leidy Magrid; Tamas, Mizik (Sam Ratulangi University, 2026)
Public programs supporting community-based ecotourism frequently face the problem of allocating limited budgets across multiple candidate villages that differ in attraction quality, service readiness, accessibility, and community capacity. This study develops a transparent decision support approach to prioritize government assistance for five community-based ecotourism villages in North Sulawesi Province, Indonesia, assessed during September to October 2025. The 4A destination framework was operationalized into 12 criteria representing Attraction, Amenity, Access, and Activity, and criterion weights were elicited through expert judgment averaging from an eight-member multistakeholder panel. The Multi Objective Optimization on the basis of Ratio Analysis method was applied to normalize the decision matrix, incorporate weights, and compute optimization scores. The resulting priority ranking was Budo (A3) with a MOORA score of 0.4036, Kakaskasen II (A4) with 0.3928, Bahoi (A1) with 0.3744, Pulisan (A2) with 0.3279, and Poopo (A5) with 0.2564. Dimension level interpretation indicates that Budo’s leading position is driven by strong amenity readiness and the most favorable access contribution, while Kakaskasen II performs strongly through activity diversity and homestay capacity but requires strengthened environmental management. Bahoi emerges as a conservation-oriented option constrained mainly by access and connectivity, whereas Pulisan and Poopo are primarily limited by minimum service readiness and travel time. A sensitivity check on the travel time weight shows stable ranks under plausible weight shifts, supporting the robustness of the prioritization. The study contributes an auditable ranking tool and criterion level development levers to guide staged, evidence-based allocation of government support for community-based ecotourism. Keywords: accessibility, community-based ecotourism, decision support system, moora, tourism village